Resistance of Biomphalaria alexandrina to Schistosoma mansoni and Bulinus truncatus to Schistosoma haematobium Correlates with Unsaturated Fatty Acid Levels in the Snail Soft Tissue - Marian Elias; Rasha S. Hanafi; Samia El-Bardicy; Ebtisam A. Hafez; Rashika El Ridi (Journal of Parasitology Research)
Only a fraction of the Biomphalaria and Bulinus snail community shows patent infection with schistosomes despite continuous exposure to the parasite, indicating that a substantial proportion of snails may resist infection. Accordingly, exterminating the schistosome intermediate snail hosts in transmission foci in habitats that may extend to kilometres is cost-prohibitive and damaging to the ecological equilibrium and quality of water and may be superfluous. It may be more cost effective with risk less ecological damage to focus on discovering the parameters governing snail susceptibility and resistance to schistosome infection. Therefore, laboratory bred Biomphalaria alexandrina and Bulinus truncatus snails were exposed to miracidia of laboratory-maintained Schistosoma mansoni and S. haematobium, respectively. Snails were examined for presence or lack of infection association with soft tissue and hemolymph content of proteins, cholesterol, and triglycerides, evaluated using standard biochemical techniques and palmitic, oleic, linoleic, and arachidonic acid, assayed by ultraperformance liquid chromatography-tandem mass spectrometry. Successful schistosome infection of B. alexandrina and B. truncatus consistently and reproducibly correlated with snails showing highly significant (up to P<0.0001) decrease in soft tissue and hemolymph content of the monounsaturated fatty acid, oleic acid, and the polyunsaturated fatty acids, linoleic, and arachidonic acids as compared to naïve snails. Snails that resisted twice infection had soft tissue content of oleic, linoleic, and arachidonic acid similar to naïve counterparts. High levels of soft tissue and hemolymph oleic, linoleic, and arachidonic acid content appear to interfere with schistosome development in snails. Diet manipulation directed to eliciting excessive increase of polyunsaturated fatty acids in snails may protect them from infection and interrupt disease transmission in a simple and effective manner.